The audacity of hope : thoughts on reclaiming the American dream - Obama, Barack (New York : Crown Publishers, 2006)
Senator Obama calls for a different brand of politics--a politics for those weary of bitter partisanship and alienated by the "endless clash of armies" we see in Congress and on the campaign trail; a politics rooted in the faith, inclusiveness, and nobility of spirit at the heart of our democracy. He explores those forces--from the fear of losing, to the perpetual need to raise money, to the power of the media--that can stifle even the best-intentioned politician. He examines the growing economic insecurity of American families, the racial and religious tensions within the body politic, and the transnational threats--from terrorism to pandemic--that gather beyond our shores. And he grapples with the role that faith plays in a democracy. Only by returning to the principles that gave birth to our Constitution, he says, can Americans repair a broken political process, and restore to working order a government dangerously out of touch with millions of ordinary Americans.--From publisher description.
Republicans and Democrats -- Values -- Our Constitution -- Politics -- Opportunity -- Faith -- Race -- The world beyond our borders -- Family.
Includes index.
Keywords: Obama, Barack; Legislators -- United States -- Biography; African American legislators -- Biography; United States. -- Congress. -- Senate -- Biography; Obama, Barack -- Philosophy; National characteristics, American; Ideals (Philosophy); United States -- Politics and government -- Philosophy; United States -- Politics and government -- 2001-; Politieke kwesties; Verenigde Staten